Plant-based sports nutrition expert fueling strategies for training, recovery, and performance - Larson-Meyer, D. Enette 1963-; Ruscigno, Matthew (Champaign, IL Human Kinetics, 2020)
Gain the plant-based advantage! Join the thousands of runners, bodybuilders, and athletes from virtually every sport who rely on foods and beverages made without animal products. Every day an increasing number of athletes, even those who are not fully vegetarian or vegan, incorporate a plant-based diet when training or recovering from competition. In Plant-Based Sports Nutrition, registered dietitians Enette Larson-Meyer and Matt Ruscigno combine decades of evidence-based research with personal experience working with--and as--vegan and vegetarian athletes to offer you a reliable and complete explanation of how, when, and why you need to plan your nutrient intake to maximize nutrition and get the best results. They will help you make smart decisions about properly fueling your body so you have the energy and stamina to boost your training and excel during competition. Learn how to get proper amounts of all essential macronutrients, vitamins, and minerals, taking into account your personal caloric needs. Draw inspiration from athletes who share how they succeed in their sports while following a plant-based way of eating. Enjoy plenty of recipes to use for training, event, and everyday nutrition needs and utilize the tailored meal plans and training strategies to properly fuel your body. Understand nutrient timing and relative energy deficiency syndrome (RED-S) as well as how to meet protein and amino acid requirements while doing light, moderate, or intense training for your sport. Get information on keto diets, tips for optimizing bone health and iron intake, and instructions for making your own fluid-replacement beverage. Whether you are a dedicated vegetarian or vegan looking to add variety to your diet or you are an athlete searching for a plant-based competitive edge, Plant-Based Sports Nutrition will help you maximize your diet for optimal performance!
Chapter 1. Gaining the Plant-Based Advantage -- Chapter 2. Getting Adequate Calories From Plant Sources -- Chapter 3. Finding the Right Carbohydrate Mix -- Chapter 4. Choosing Smart Fat Over No Fat -- Chapter 5. Building Muscle Without Meat -- Chapter 6. Optimizing Bone Health -- Chapter 7. Boosting Iron Intake and Absorption -- Chapter 8. Breaking Free of Multivitamin Dependence -- Chapter 9. Prioritizing Food and Fluids Before, During, and After Events -- Chapter 10. Choosing Whether to Supplement -- Chapter 11. Reducing Muscle Cramps and Inflammation -- Chapter 12. Creating a Customized Meal Plan -- Chapter 13. Adapting the Plan to Manage Weight -- Chapter 14. Whipping Up Quick Plant-Based Meals and Snacks -- Chapter 15. Recipes -- Appendix A. Energy Costs of Physical Activity -- Appendix B. Food Guidance Systems -- Appendix C. Foods Containing FODMAPs -- Appendix D. Glycemic Index of Common Foods -- Appendix E. Dietary Reference Intakes for Vitamins and Minerals -- Appendix F. Metric Conversions for Common Measures.
Includes bibliographical references
Keywords: Physical fitness; Athletes -- Nutrition; Veganism -- Health aspects